Facile preparation and electrochemistry performance of quasi solid-state polymer lithium–sulfur battery with high-safety and weak shuttle effect. (November 2019) - Long, Canghai; Li, Libo; Zhai, Mo; Shan, Yuhang
Abstract: With a higher theoretical energy density relative to Li ion batteries (LIBs) and abundance of elemental sulfur, the lithium sulfur (L-S) batteries were regarded as the promising next-generation high energy density storage devices for the protable electronics and electric vehicles. However, there were some main challenges stemming from the polysulphide dissolution and the high flammability of the sulfur which limited the further application of the lithium sulfur Li–S batteries. Here, we reported a facile method to prepare the quasi solid-state Li–S batteries (LSBs) with sulfur nanoparticles electrode and PVDF-based solid polymer electrolyte (SPE), which had less flammability, electrochemical stability and ionic conductivity. The prepared PVDF-based solid polymer electrolyte possessed the conductivity ∼10 −4  S cm −1 at 25 °C and the lithium ions transference number of 0.49. GITT demonstrated the Li + transport diffusion mechanism in the active S@nano-TiO2 cathode of the quasi solid-state lithium–sulfur battery. It was important to get the smooth diffusion path for the lower resistance in the charging process. Because of the high content and the sulfur uniform distribution on the nanoscale titanium dioxide (TiO2 ), the S@nano-TiO2 cathode exhibited its performance. The first cycle discahrge specific capacity was 1160 mAh g −1 at 0.15C at room temperature. Graphical abstract: Image 1 Highlights: A new strategy was put forward for the few solubilities of safe LiPSs. LiPSs mainly consisted of nano-TiO2 @S cathode and PVDF-based solid electrolyte. GITT demonstrated Li + transport diffusion mechanism in nano-TiO2 @S cathode. Initial discahrge specific capacity is 1160 mAh g −1 at 0.15C at room temperature.